Exile and the Kingdom: Integration of an Exiled Family - Porto, Bráulio (Journal of analytical psychology, 2022)
The subject of exile is a ubiquitous global theme. The result of multiple factors, it insinuates itself into events affecting people’s daily lives and the development of countries. Beyond politics, a psychological reading enables us to reflect on its impact, not only on the individual or group but also in relation to the exiled family. The concept of a mythical or archetypal family can help us to clarify what emerges from contact between two communities and the challenges in their encounter. The study of a specific case – Portuguese families adjusting to life in a French‐speaking region of Switzerland – reveals a pattern reproduced elsewhere, even though separate in time and space. The cultural shock emanating from a background and approach of different dynamics leads to psychological resistance on both sides – and to a negative prognosis for cultural integration. Analytical work with exiled children and adolescents allows us to glimpse how this theme intertwines with personal psychologies, pointing to its creative solution through the resolution of conflict and openness to diversity – as carried forward by new generations. It is they who are open to multicultural values, showing simultaneously a respect for ancestry and a desire for renewal. La question de l’exil est un thème omniprésent et global. Le résultat de multiples facteurs, l’exil s’insinue dans des événements qui affectent la vie quotidienne des gens et le développement des pays. Au‐delà de la politique, une lecture psychologique nous permet de réfléchir à son impact, non seulement sur l’individu ou le groupe mais aussi en relation avec la famille exilée. Le concept d’une famille mythique ou archétypale peut nous aider à clarifier ce qui émerge du contact entre deux communautés et les défis liés à cette rencontre. L’étude d’un cas particulier – celui des familles portugaises s’ajustant à la vie dans la région Suisse de langue française – révèle le schéma qui se répète ailleurs, bien que de manière distincte dans le temps et dans l’espace. Le choc culturel émanant d’un « background » et d’une approche des différentes dynamiques mène à une résistance psychologique des deux côtés – et à un mauvais pronostic en ce qui concerne l’intégration culturelle. Le travail analytique avec des enfants et des adolescents exilés nous permet d’entrevoir comment ce thème s’entremêle aux psychologies personnelles, montrant sa solution créative au travers de la résolution de conflit et de l’ouverture à la diversité – telle qu’elle est portée par les nouvelles générations. Ce sont elles qui sont ouvertes aux valeurs multiculturelles, montrant simultanément un respect pour ce qui est ancestral et un désir de renouveau. Der Topos Exil bildet ein allgegenwärtiges globales Thema. Als Ergebnis mehrerer Faktoren schleicht er sich in Ereignisse ein, die das tägliche Leben der Menschen und die Entwicklung von Ländern beeinflussen. Jenseits der Politik ermöglicht uns eine psychologische Auffassung, seine Auswirkungen nicht nur auf den Einzelnen oder die Gruppe, sondern auch in Bezug auf die Familie im Exil zu reflektieren. Das Konzept einer mythischen oder archetypischen Familie kann uns helfen zu klären, was aus dem Kontakt zweier Gemeinschaften und den Herausforderungen ihrer Begegnung entsteht. Die Untersuchung eines konkreten Falles – portugiesische Familien, die sich an das Leben in der Westschweiz angepaßt haben – zeigt ein Muster, das anderswo reproduziert wird, wenn auch zeitlich und räumlich getrennt. Der Kulturschock, der auf dem Hintergrund und den Herangehensweisen unterschiedlicher Dynamiken auftritt, führt auf beiden Seiten zu psychologischen Widerständen – und zu einer negativen Prognose für die kulturellen Integration. Die analytische Arbeit mit Kindern und Jugendlichen im Exil läßt erahnen, wie sich dieses Thema mit persönlichen Psychologien verschränkt und dabei auf seine kreative Lösung durch Konfliktlösung und Offenheit für Vielfalt – wie es von neuen Generationen getragen wird – hinzielt. Sie sind es, die offen für multikulturelle Werte sind und gleichzeitig Respekt vor der Herkunft und den Wunsch nach Erneuerung zeigen. Il tema dell’esilio è un tema globale onnipresente. Il risultato di molteplici fattori, si insinua in eventi che influenzando la quotidianità delle persone e lo sviluppo dei Paesi. Oltre la politica, una lettura psicologica ci consente di riflettere sul suo impatto, non solo sull’individuo o sul gruppo, ma anche in relazione alla famiglia esiliata. Il concetto di una famiglia mitica o archetipica può aiutarci a chiarire ciò che emerge dal contatto tra due comunità e le sfide nel loro incontro. Lo studio di un caso specifico ‐ famiglie portoghesi, che si adattano alla vita nella regione francofona della Svizzera ‐ rivela uno schema riprodotto altrove, anche se separato nel tempo e nello spazio. Lo shock culturale derivante da un background e da un approccio di dinamiche diverse porta alla resistenza psicologica da entrambe le parti ‐ e ad una prognosi negativa per l’integrazione culturale. Il lavoro analitico con bambini e adolescenti in esilio ci permette di intravedere come questo tema si intreccia con le psicologie personali, indicando la sua soluzione creativa tramite la risoluzione del conflitto e l’apertura alla diversità, portata avanti dalle nuove generazioni. Sono loro che sono aperti ai valori multiculturali, mostrando allo stesso tempo un rispetto per le origini e il desiderio di rinnovamento. Тема изгнания вездесущая и глобальная. Являясь результатом действия множества факторов, она проникает в события, влияющие на повседневную жизнь людей и развитие стран. Помимо политики, психологическое прочтение позволяет нам задуматься о ее влиянии не только на человека или группу, но и на семью изгнанника. Концепция мифической или архетипической семьи может помочь нам прояснить, что возникает в результате контакта между двумя сообществами, с какими проблемами они сталкиваются. Изучение конкретного случая ‐ португальских семей, приспосабливающихся к жизни во франкоговорящем регионе Швейцарии – помогает увидеть паттерн, который мы видим и в других местах, хотя и разделенных во времени и пространстве. Культурный шок приводит к психологическому сопротивлению с обеих сторон и к негативному прогнозу относительно культурной интеграции. Аналитическая работа с детьми и подростками в изгнании позволяет нам увидеть, как эта тема переплетается с их личностными особенностями, указывая на ее творческое решение через разрешение конфликтов и открытость к разнообразию, продвигаемую новыми поколениями. Именно те, кто открыт мультикультурным ценностям, демонстрирует одновременно и уважение к предкам и стремление к обновлению. La cuestión del exilio es un tema global ubicuo. Resultante de factores múltiples, se insinúa a sí mismo en eventos que afectan la vida cotidiana de las personas y el desarrollo de los países. Más allá de la política, una lectura psicológica nos permite reflexionar sobre su impacto, no solo en el individuo o grupo, sino también en relación con la familia exiliada. El concepto de familia mítica o arquetípica puede ayudarnos a clarificar aquello que emerge del contacto entre dos comunidades y los desafíos en ese encuentro. El estudio de un caso específico – familias portuguesas, adaptándose a vivir en la región de habla francesa de Suiza – revela un patrón que se reproduce en otros lugares, aún la separación en tiempo y espacio. El shock cultural que emana de un trasfondo y enfoque de dinámicas diferentes conduce a una resistencia psicológica en ambos lados – y a una prognosis negativa para la integración cultural. El trabajo analítico con niños y adolescentes exiliados nos posibilita vislumbrar como este tema se entrelaza con las psicologías personales, indicando una solución creativa a través de la resolución de conflictos y la apertura a la diversidad – llevada adelante por las nuevas generaciones. Son éstas quienes están abiertas a los valores multiculturales, mostrando simultáneamente un respeto por lo ancestral y el deseo de renovación. 流放与王国:流放家庭的整合 流放是一个无处不在的全球性主题。在多重因素的作用下, 它渗透进各种事件之中, 对人们的日常生活和国家发展产生影响。除了政治的途径, 心理的解读可以使我们反思其影响, 这一影响不仅涉及个人或群体, 也涉及到流亡中的家庭。神话或原型家庭的概念可以帮助我们明析在两个社群接触之际到底发生了什么, 以及他们的相遇所带来的挑战是怎样的。本文对一个特定案例进行了研究——这是一个葡萄牙家庭, 正在尝试适应瑞士法语区的生活——这个案例揭示了一种在其它地方, 尽管在不同时空之中, 也在重复的模式。来自于不同背景所散发出来的文化冲击, 以及不同动力的取向导致了双方的相互抵触, 以及对文化融合的负面预测。对流放儿童和青少年的分析工作让我们得以窥见这一主题如何与个人心理交织在一起, 如何通过解决冲突, 以及对多样性的开放态度, 来实现一种创造性的解决方案——正如新一代所发扬光大的那样。他们对多元文化的价值观持开放态度, 同时表现出对祖先的尊重和对更新的渴望。 A questão do exílio é um tema global onipresente. Resultado de múltiplos fatores, ele se insinua em eventos que afetam o cotidiano das pessoas e o desenvolvimento dos países. Indo além da política, uma leitura psicológica nos permite refletir sobre seu impacto, não apenas no indivíduo ou grupo, mas também em relação à família exilada. O conceito de família mítica ou arquetípica poderia nos ajudar a esclarecer o que emerge do contato entre duas comunidades e os desafios do seu encontro. O estudo de um caso específico – famílias portuguesas, em adaptação à vida na região francófona da Suíça – revela um padrão reproduzido em outros lugares, embora separado no tempo e no espaço. O choque cultural trazido pela aproximação de dinâmicas tão distintas, resulta em um quadro de resistência psicológica em ambos os lados, elevando a um prognóstico negativo quanto à sua integração cultural. O trabalho analítico com crianças e adolescentes exilados nos permite vislumbrar como esse tema se entrelaça com as psicologias pessoais, apontando para sua solução criativa através da resolução de conflitos e abertura à diversidade protagonizada pelas novas gerações. São elas que se encontram abertas aos valores multiculturais, mostrando simultaneamente respeito à ancestralidade e desejo de renovação.